2008
DOI: 10.1107/s0021889808028264
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing three-dimensional shape envelopes from time-resolved small-angle X-ray scattering data

Abstract: Modern computing power has made it possible to reconstruct low-resolution, three-dimensional shapes from solution small-angle X-ray scattering (SAXS) data on biomolecules without a priori knowledge of the structure. In conjunction with rapid mixing techniques, SAXS has been applied to time resolve conformational changes accompanying important biological processes, such as biomolecular folding. In response to the widespread interest in SAXS reconstructions, their value in conjunction with such time-resolved dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The sizes and shapes deduced from analyses of cryo-EM images are in agreement with structures we obtain independently from 3D reconstructions of SAXS form factors (Konarev et al 2006;Lipfert et al 2007a;Lamb et al 2008) and those we predict by molecular dynamics (MD) software recently developed (Jonikas et al 2009) for simulating spatial conformations of RNA secondary structures. With this combination of approaches, we demonstrate that the 3D anisotropy of long ssRNAs can be directly deduced from analysis of their cryo-EM images.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The sizes and shapes deduced from analyses of cryo-EM images are in agreement with structures we obtain independently from 3D reconstructions of SAXS form factors (Konarev et al 2006;Lipfert et al 2007a;Lamb et al 2008) and those we predict by molecular dynamics (MD) software recently developed (Jonikas et al 2009) for simulating spatial conformations of RNA secondary structures. With this combination of approaches, we demonstrate that the 3D anisotropy of long ssRNAs can be directly deduced from analysis of their cryo-EM images.…”
Section: Introductionsupporting
confidence: 65%
“…Whereas high-field nuclear magnetic resonance (NMR) can directly and reliably probe the structures of short ssRNAs in solution (Flinders and Dieckmann 2006), this technique cannot be used for molecules longer than 1000 nt because of their slow rotational diffusion. Third, while low-resolution three-dimensional (3D) reconstructions of RNAs in solution can be obtained from small-angle X-ray scattering (SAXS) reconstructions, the method has generally been applied to RNA molecules z200 nt in length or shorter, often containing one dominant secondary structure (Lipfert et al 2007a(Lipfert et al ,b, 2008Lamb et al 2008). Applying this technique to larger RNAs is considerably more difficult because the scattered intensity relevant for overall size determination lies at very small angles, close to the incident beam.…”
Section: Introductionmentioning
confidence: 99%
“…The folding of P4-P6 has been followed in multiple studies, with folding rate constants of 2-30 s −1 observed across a range of conditions (52)(53)(54)(55)(61)(62)(63)(64)(65). However, interpretation of these overall rate constants has been stymied by a lack of knowledge of which individual folding steps were followed and rate limiting.…”
Section: Resultsmentioning
confidence: 99%
“…The control afforded by this well-behaved, established system provides an opportunity to deepen understanding and develop and test generalizable principles beyond this model system, provided that a detailed framework is in place to provide context for interpretation. Here, we use single-molecule FRET (smFRET) with a series of P4-P6 mutants to isolate and measure specific folding transitions, extending beyond measurements of overall folding rates (52)(53)(54)(55)(61)(62)(63)(64)(65) and constructing a kinetic and thermodynamic framework for P4-P6 RNA. This framework defines a preferred folding pathway, allows this pathway and the partitioning of states to be interpreted in structural terms, helps to uncover the origin of the effects of mutations on folding rates and pathways, and suggests a generalized framework for considering RNA tertiary folding.…”
mentioning
confidence: 99%
“…To evaluate the quality of captured scattering profiles the technique of Lamb et al (2008) was followed to calculate the signal-to-noise ratio (S/N) as…”
Section: Scattering Measurementsmentioning
confidence: 99%